Relationship between blood pressure variables (Systolic Blood Pressure, Diastolic Blood Pressure, Pulse Pressure, and Mean Arterial Pressure) and left atrial measurements among hypertensive subjects in a Tertiary Hospital in South-South Nigeria - Aiwuyo Osarume Henry; Ejiroghene Martha Umuerri; Aisosa Ogbomo; John Osaretin Osarenkhoe; Austine Osemwegie Obasohan (Journal of Clinical and Preventive Cardiology, 2022)
Background: Hypertension is known to impact significant changes on the heart causing left ventricle diastolic dysfunction which precedes a sequel of anatomical and functional changes in the left atrium. Since hypertension remains the leading cause of diastolic dysfunction in the heart, it is expedient to determine how changes in the blood pressure of patients relate to measures of left atrial (LA) indices. Aims and Objectives: to determine how changes in blood pressure parameters relate to measures in LA indices. Materials and Methods: The study was a descriptive cross-sectional appraisal of 200 hypertensive patients and 100 normotensive controls (matched for age and sex in a 2:1 ratio) using electrocardiography and echocardiography. Participants were recruited from the cardiology clinics in Delta State University Teaching Hospital (DELSUTH), Oghara. Results: The mean age of the study population was 58.7 ± 13.96 (58.42 ± 13.29 for hypertensives and 59.26 ± 15.27 for controls) years, while the median age was 59 years. The female-to-male ratio was 1.06 among cases and 1.27 among the controls. The LA size (volumes and linear diameter) was significantly larger in the hypertensive group compared to the control arm. LA maximum volume correlated significantly with average systolic blood pressure, pulse pressure, and mean arterial pressure. LA pre A wave volume and LA minimum volume correlated significantly with average systolic blood pressure and pulse pressures. Conclusion: Hypertensive patients have larger LA volumes than normotensive controls. The size of the left atrium relates positively with blood pressure variables.